“PERGILAH, JADIKANLAH SEMUA BANGSA MURID-KU”: PEWARTAAN GEREJA YANG SINODAL DAN ADAPTIF - Benedictus Eric Hariyanto (Aggiornamento, 2022)
This paper is focused on the study of the synodal and adaptive movements of the Church, which cannot be separated from the Church's mission of proclaiming the Gospel. The focus of writing this paper cannot be separated from two concrete situations: the 2021-2024 Synod of Bishops and the Covid-19 pandemic which is still looming over the direction of the Church's movement to this day. The purpose of writing this paper is to revitalize the identity of the Church by proclaiming the good news of salvation in a new-world realities. Revitalizing the Church's identity that I offer is to become more synodal and adaptive Church. I used the method of literature study and comparing it with biblical text, especially Matthew 28:19, “Therefore, go and make disciples of all nations…” This paper finds that in the midst of its existence in the “new” world, the Church is asked to revitalize its identity while proclaiming the Gospel. The relevance of this paper is that, the Church is required to revitalize its identity in its task of proclaiming the Gospel to every creature, as mandated by Jesus, the Teacher. Identity revitalization can be realized by becoming a synodal and adaptive Church.